One-step electrodeposition of ZnO/graphene composites with enhanced capability for photocatalytic degradation of organic dyes - Lu, Hui; Sha, Simiao; Li, Tong; Wen, Qian; Yang, Shaolin; Wu, Jiandong; Wang, Kang; Sheng, Zhilin; Ma, Jinfu (Frontiers in Chemistry, 2022)
Zinc oxide (ZnO) is a popular semiconductor used in catalysts due to its wide bandgap and high exciton binding energy. However, the photocatalytic performance of ZnO was compromised by its insufficient electron-hole separation efficiency and electron transfer rate. Herein, a ZnO-reduced graphene oxide (rGO) composite solid catalyst was synthesized on the fluorine-doped tin oxide (FTO) conductive glass substrate by a one-step electrodeposition method using lithium perchlorate (LiClO4) as the supporting electrolyte. SEM, Raman, FTIR, and XRD characterizations confirmed the deposition of ZnO and the reduction of graphene oxide (GO). Owing to the cooperative effect between rGO and ZnO, the as-prepared ZnO-rGO composites show much enhanced photocatalytic degradation ability compared with ZnO nanorods. By optimizing the conditions of electrodeposition of ZnO-rGO composites, the degradation rate of methylene blue (MB) can reach 99.1% within 120 min. The simple preparation and the excellent performance could endow the ZnO-rGO composites with promising application in practical dye-polluted water treatment.